Islam: The Religion of Peace - Ibrahim, Muhammad (Riyadh Darussalam, 2007)
This book by Muhammad Ibrahim presents Islam as a faith centered on peace, justice, and moral guidance. It addresses common misconceptions about the religion, emphasizing its teachings on nonviolence, social harmony, and ethical living. The work serves as an accessible introduction for both Muslims and non-Muslims seeking to understand the peaceful principles of Islam.
Keywords: Islam $1 (BDoctrines | Islam $1 (BPeace and nonviolence | Islamic ethicss